ENGINEERING OF THE BOOST SYSTEM FOR SMALL-SIZE GAS-TURBINE ENGINE WITH PULSE-DETONATION MODULE - M. I. Erofeev; V. V. Parievskiy (Научный вестник МГТУ ГА, 2017)
One of the promising ways to boost the gas turbine engine is to install a pulse detonation module in the exhaust case. Research on the effectiveness of the developed module in the expenditure thermal vacuum chamber, providing a complete simulation of these terms and conditions, requires unique equipment, as well as the significant financial and oper- ating costs. Accordingly ,it is more efficient to conduct performance and effectiveness assessment of the pulse detonation module using the existing test rigs, modified to partially simulate flight conditions comprising: a platform with the studied gas turbine engine (GTE), a power plant on a movable platform, pressurization system pipeline from an auxiliary power unit (APU) to the test engine, fuel and electrical systems of the test rig. The article presents small-size GTE pressurization system design results. The pipeline design is based on the conditions of mutual arrangement of the studied GTE and APU test cell. The choice of design solutions for production and assembly of components of the pressurization system, and the results are presented algorithm and calculating geometrical parameters ejector providing the required pressure and air flow temperature at the inlet to the studied engine. As a result, the research reasonably determined the structural diagram of the boost system test rig, providing a partial simulation of flight conditions at the inlet to the small-sized turbine engine. There were defined the necessary geometry and gas-dynamic properties of the gas ejector, the use of which as part of test rig pres- surization system will start the series of studies, according to the pulse detonation performance of the module.